Effect of drying methods on properties of green curry powder - Natthacha Chaloeichitratham; Pornkanya Mawilai; Thadchapong Pongsuttiyakorn; Pimpen Pornchalermpong (My University, 2018)
In this study, the effects of two drying methods: hot-air and freeze drying for Thai green curry paste in a terms of drying time and qualities have been investigated. The hot-air drying was carried out in tray dryer at temperature of 50, 60 and 70 °C. The freeze drying was carried out in freeze dryer at freezing temperature of -20°C, primary drying temperature of -10°C and secondary drying temperature of 50°C. Moisture content, water activity, colour, bulk density, and total phenolic content (TPC) were determined in samples. Freeze dried sample had significantly (p<0.05) lower moisture content, water activity, bulk density, total colour difference and browning index than hot air dried samples. For antioxidant activity, the results showed hot-air drying at 70°C effected highest TPC similar to freeze drying.
Keywords: Tray; Browning; Water activity; Microencapsulation and Drying Processes